Analysis of Religious Moderation in Ustadz Adi Hidayat's YouTube Content - Vania Daffa Yusriyah Daulay; Khatibah Khatibah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Digital media, especially YouTube, has become an effective platform for Islamic preaching (dakwah) to convey religious messages in a moderate, interactive, and contextual manner in the global digital era. This study aims to analyze the content of dakwah messages concerning religious moderation in the sermons of Ustadz Adi Hidayat. This research employs a qualitative approach using content analysis techniques. The methodology involves documenting sermon videos, transcribing the dakwah content, recording metadata, and analyzing the data based on religious moderation, including wasathiyah (moderation), justice, tolerance, and anti-extremism. The findings indicate that Ustadz Adi Hidayat’s sermons on YouTube contain 27 quotations reflecting the values of religious moderation per the official indicators of the Indonesian Ministry of Religious Affairs. The dominant value that emerges is the balance between the relationship with God and fellow human beings (habluminallah–habluminannas), followed by tolerance, anti-violence, and social ethics. The dakwah messages are conveyed contextually and persuasively, integrating Islamic teachings with the social realities of Indonesia. These sermons emphasize the importance of moderation in religious practice and demonstrate the effectiveness of digital media in disseminating peaceful, tolerant, and balanced Islamic values in the post-modern era. This study concludes that Ustadz Adi Hidayat’s sermons on YouTube predominantly communicate the values of religious moderation in a balanced and relevant manner, consistent with the official concept endorsed by the Indonesian Ministry of Religious Affairs.